INFLUENCE OF MAGNETIC FIELD AND NANOPARTICLE TRANSPORT ON BOUNDARY LAYER FLOW: A NUMERICAL INVESTIGATION - Adekoya, Odunayo M; Akinfenwa, Olusheye A; Fenuga, Olugbenga J. (FUDMA Journal of Sciences, 2026)
A study of magnetic field and nanoparticle transport on boundary layer flow of magnetohydrodynamic (MHD) nanofluid over a stretching vertical surface has been analyses numerically. By introducing appropriate similarity variables, the governing partial differential equations describing momentum, energy and concentration were reduced to nonlinear coupled Ordinary Differential Equations (ODE). Utilizing the shooting technique along exponentially fitted Simpson type block method is used to solve the Boundary value problems using computational software MAPLE 16. Numerical results for velocity, temperature and concentration profiles are presented and the effect of key parameters including magnetic field strength, Brownian motion, thermophoresis, internal heat generation and thermal radiation was analyzed. The computed Nusselt number and Sherwood number demonstrate excellent agreement with existing literature, confirming the stability and accuracy of the method used. The results reveal that magnetic effects reduce fluid velocity while thickening thermal and concentration boundary layers, whereas buoyancy forces, radiation and internal heat generation enhance momentum and heat transport. Nanoparticle diffusion is significantly influenced by thermophoresis and Brownian motion effects